Analisis keberhasilan produk makanan halal: Dinamika sertifikasi halal produk Samyang di Indonesia - Aisi, Salwa Richadatul (Journal of Halal Industry Studies, 2023)
This study examines the impact of halal certification on Samyang products in Indonesia, focusing on increased sales after obtaining the certification. Before certification, Muslim consumers were hesitant about Samyang's content, but sales increased after obtaining halal certification because this concern was addressed. The research method used is descriptive qualitative. From the research findings, it can be concluded that countries need to ensure the halal status of products circulating in the market, especially in Muslim-majority countries like Indonesia. The halal certification process by MUI provides assurance of product halalness, as seen in Samyang products. After obtaining certification, the product experienced increased sales as Muslim consumers were no longer hesitant about its halal status. Thus, halal certification is not only important to meet the needs of Muslim consumers but also has the potential to increase product sales.